Novel One Pot Microwave Irradiated Synthesis and Antimicrobial Activities of Some Pyrazolinylbutanediones - BAJIA, B.; RAO, N.S.; NYATI, M.; SRIVASTAVA, Y.K. (Asian Journal of Chemistry, 2010)
New 1-(3,5-diaryl-2-pyrazolinyl)-1,3-butanediones have been synthesized by condensation of 3,5-diaryl-2-pyrazolines with ethyl acetoacetate using microwave irradiation. The synthesized compounds were characterized by their elemental and spectral data and screened for their antibacterial activity.